Clinical Outcomes of Unicompartmental Knee Arthroplasty: A Comprehensive Review - Domagała, Wojciech; Salamon, Dariusz; Stachowiak, Julia; Sosin, Julia; Pilarz, Anna; Zwierzchowska, Maria; Sojka, Aleksandra (Quality in Sport, 2025)
Unicompartmental knee arthroplasty (UKA) has gained significant attention in recent years as an important treatment option for isolated compartmental osteoarthritis of the knee, offering distinct advantages over Total Knee Arthroplasty (TKA). This review article aims to comprehensively analyze the clinical outcomes of UKA, focusing on surgical techniques, patient satisfaction, functional improvement, implant survivorship, complications and future directions. Through an examination of current literature and clinical studies, this review provides valuable insights into the efficiency and limitations of unicompartmental knee arthroplasty as a surgical intervention for managing unicompartmental knee pathology, with an emphasis on its growing role in modern orthopedic practice. AIM OF THE STUDY: The aim of the study is to evaluate the available knowledge about surgical techniques and clinical outcomes of Unicompartmental Knee Arthroplasty, highlight its strengths and weaknesses and benefits compared to Total Knee Arthroplasty. MATERIALS AND METHODS: The literature available in PubMed, Google Scholar, BMJ, JBJS, JOSR, database was reviewed using the following keywords: “UKA”, “Knee”, “Arthroplasty”, “TKA”, “Recovery” , “Clinical Outcomes”. RESULTS: A review of the literature underscore the importance of tailored treatment decisions, emphasizing that UKA is best suited for patients with unicompartmental osteoarthritis who meet strict selection criteria. Its benefits make it a strong choice in such cases, but careful consideration is needed for long-term success.